2016
DOI: 10.4102/sajpsychiatry.v22i1.976
|View full text |Cite
|
Sign up to set email alerts
|

Copeptin levels and blood lipid profile in borderline patients with or without self-mutilation

Abstract: PurposeSelf-mutilation, known as self-harming behaviour of an individual without the intention of suicide, is commonly observed in individuals with borderline personality disorder. The objective of this study is to compare copeptin levels that are known to be related to aggressive behaviour and blood lipid profiles in borderline patients with and without self-mutilation.MethodsTwenty patients with self-mutilation [SM(+)] and 20 patients without self-mutilation [SM(−)] between the ages of 18 and 49, diagnosed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Studies on the correlation between cholesterol levels and serotonin demonstrated that serotonin levels were also low in individuals with low cholesterol 51,52 . Studies demonstrated that low cholesterol levels decreased serotonin receptor sensitivity by reducing membrane fluidity, and low cholesterol levels reduced 5-HT neurotransmission in presynaptic and postsynaptic regions 53 . In a study conducted by Atmaca et al, it was found that serum cholesterol and leptin levels were lower in patients with BPD when compared to healthy controls, and it was reported that low leptin and cholesterol levels were negatively associated with the impulsivity, aggression and suicidal ideation dimensions of the disorder 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the correlation between cholesterol levels and serotonin demonstrated that serotonin levels were also low in individuals with low cholesterol 51,52 . Studies demonstrated that low cholesterol levels decreased serotonin receptor sensitivity by reducing membrane fluidity, and low cholesterol levels reduced 5-HT neurotransmission in presynaptic and postsynaptic regions 53 . In a study conducted by Atmaca et al, it was found that serum cholesterol and leptin levels were lower in patients with BPD when compared to healthy controls, and it was reported that low leptin and cholesterol levels were negatively associated with the impulsivity, aggression and suicidal ideation dimensions of the disorder 31 .…”
Section: Discussionmentioning
confidence: 99%